Phase II of Nixon's new economic policy - Carl Landauer (Intereconomics, 1971)
In order to fight Inflation President Nixon has resorted to means of Interference which the US economy Is not accustomed to. The following article deals with the Intricacies arising from Phase II of his price- and wage-policy.
Keywords: 330; USA